Penerapan Sistem Informasi Penelusuran Perkara (Sipp) Sebagai Sarana Kontrol Dalam Penanganan Berkas Perkara Di Kepaniteraan Muda Pengadilan Negeri Cirebon Kelas 1B - Siti Hawa; Mohamad Rana (Hukum, 2026)
The digitalization of case administration is essential to establishing simple, prompt, transparent, and accountable judicial services. This study aims to analyze the implementation and effectiveness of the Case Tracking Information System (SIPP) as an instrument for controlling case administration at the Cirebon District Court Class IB and to identify the constraints affecting its implementation. The study employs an empirical legal method with a socio-legal approach and a qualitative case study design. Data were collected through direct observation, semi-structured interviews with court personnel involved in using and supervising SIPP, and a review of legislation, Supreme Court policies, administrative documents, and previous studies. The data were interactively analyzed through condensation, categorization, presentation, triangulation, and conclusion drawing. The findings indicate that SIPP supports the integrated recording, updating, tracking, and monitoring of case administration. Its effectiveness is reflected in improved timeliness, completeness, accuracy, traceability, and transparency of case data. Nevertheless, its implementation remains affected by differences in users’ technological competence, workload, network stability, hardware conditions, technical disruptions, and inconsistencies between digital information and source documents. The study concludes that SIPP’s effectiveness depends on the integration of a reliable system, competent users, clearly assigned responsibilities, systematic data verification, adequate technical support, and continuous administrative monitoring.